Scratch-resistant wood decorative plate and manufacturing process thereof

By coating soy protein-based adhesive and treated kraft paper base paper on the surface of the wooden decorative board and using vinyl modified epoxy resin, the problem of scratching and scratching of traditional wooden decorative boards is solved, and the scratch resistance and wear resistance of the board are significantly improved.

CN119615662AInactive Publication Date: 2025-03-14SHENZHEN FENGMEIJIA DECORATION MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411883311.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional wooden decorative boards are prone to scratches, scratches, wear and other problems during use, especially in places with high frequency contact, with significant surface damage, affecting the decoration effect and the service life of the material.

Method used

By coating soy protein-based adhesive on both sides of the surface of the poplar board and coated with kraft paper base paper impregnated with acrylic-silicon sol composite liquid, the scratch resistance of the board is enhanced.

Benefits of technology

It significantly improves the scratch resistance, wear resistance and stain resistance of wooden decorative boards, extends the service life of the material, and improves the decorative effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a scratch-resistant wood decorative plate and a manufacturing process thereof, and relates to the technical field of decorative plates. The two sides of the surface of the poplar board are coated with the soybean protein-based adhesive, then the two faces, coated with the soybean protein-based adhesive, of the poplar board are coated with the kraft paper body paper B, sulfhydrylated aluminum oxide is added into the soybean protein-based adhesive, and the binding force between the poplar board and the kraft paper body paper B is enhanced. According to the preparation method disclosed by the invention, firstly, raw kraft paper is immersed into an acrylic acid-silica sol composite solution to obtain raw kraft paper A subjected to immersion treatment, the acrylic acid-silica sol composite solution is prepared from sulfhydrylated silicon dioxide sol and an acrylic emulsion, and the density of the composite solution is improved by adding silica sol; the acrylic acid-silica sol composite liquid has excellent wear resistance, the toughness of the coating is improved, and the decorative plate has good scratch resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of decorative plates, in particular to a scratch-resistant wooden decorative plate and a manufacturing process thereof. Background Art

[0002] Wood decorative panels have become an important material in the building decoration industry due to their natural beauty, strong environmental protection and easy processing. However, traditional wood decorative panels are prone to scratches, scuffs, wear and tear during use, especially in places with high frequency of contact, where surface damage is significant, affecting the decorative effect and service life of the material.

[0003] Most of the existing wooden decorative panels are surface treated by wood grain paper veneer, wood veneer or wood composite materials. Although these materials have improved the aesthetics and durability of wooden decorative panels to a certain extent, they are still insufficient in terms of scratch resistance, wear resistance and stain resistance. In order to solve this problem, the existing technology usually coats a protective layer on the surface of wooden decorative panels. Although the existing surface coating can improve the scratch resistance to a certain extent, the coating is prone to aging and falling off during long-term use, resulting in a decrease in the aesthetics and functionality of the decorative panels.

[0004] In order to solve the above problems and improve the scratch resistance of decorative boards, the present invention provides a scratch-resistant wooden decorative board and a manufacturing process thereof. Summary of the invention

[0005] The object of the present invention is to provide a scratch-resistant wooden decorative board and a manufacturing process thereof, so as to solve the problems raised in the prior art.

[0006] To achieve the above object, the present invention provides the following technical solutions: A manufacturing process for a scratch-resistant wooden decorative board comprises the following steps: Step 1: Take acrylic emulsion and mercapto-silica sol, stir for 1-2 hours to obtain acrylic acid-silica sol composite liquid; Step 2: Take acrylic acid, epoxy resin, dithiodipropionic acid, tetrabutylammonium bromide, and hydroquinone, heat to 90-95°C and stir for 1-2h, and continue to heat to 105-110°C for reaction for 2-3h to obtain a vinyl-modified epoxy resin; Step 3: Take kraft paper, immerse it in acrylic acid-silica sol composite solution for 2-3 hours, and dry it to obtain kraft paper A after impregnation treatment; then coat vinyl-modified epoxy resin on both surfaces of the kraft paper A after impregnation treatment, and dry it to obtain kraft paper B; Step 4: Take a poplar board and evenly apply the soy protein-based adhesive on both sides of the surface of the poplar board, cover both sides of the poplar board coated with the soy protein-based adhesive with kraft paper B, press at 80-85°C for 10-15 minutes, then irradiate with ultraviolet light for 10-15 seconds, and dry to obtain a scratch-resistant wooden decorative board.

[0007] More optimally, in step one, the preparation method of the acrylic emulsion is: take methyl methacrylate, butyl acrylate, styrene, and acrylic acid, mix them evenly to obtain a monomer mixed solution; take deionized water, polyoxyethylene nonylphenol ether, and sodium dodecylbenzene sulfonate, stir them evenly, heat them to 40-45°C, add the monomer mixed solution dropwise while stirring, and stir for 10-15 minutes to obtain an emulsion; take deionized water, polyoxyethylene nonylphenol ether, sodium dodecylbenzene sulfonate, and sodium bicarbonate, heat them to 85-88°C, add the emulsion, react for 5-6 hours, add dimethylethanolamine dropwise while stirring, and stir for 20-30 minutes to obtain an acrylic emulsion.

[0008] More optimally, in step 1, the mass ratio of acrylic emulsion to mercapto-silica sol is (80-85):5.

[0009] More optimally, in step one, the preparation method of the thiolated silica sol is: take γ-mercaptopropyltrimethoxysilane and ethanol, stir evenly to obtain a γ-mercaptopropyltrimethoxysilane solution; take the silica sol, heat it to 60-65°C, add the γ-mercaptopropyltrimethoxysilane solution dropwise, stir for 5-7h, and obtain the thiolated silica sol.

[0010] More optimally, the preparation method of the silica sol is: take ethanol and ammonia water, stir evenly at 60-70°C, then add tetraethyl orthosilicate dropwise, continue stirring at 60-65°C for 1-2h, and age for 30-40min to obtain the silica sol.

[0011] More optimally, in step four, the preparation method of the soy protein-based adhesive is: take deionized water, add borax, sodium sulfite, soy protein, and thiolated alumina, heat to 55-60°C, stir for 1-2h, cool to 25-30°C, add propylene glycol triglycidyl ether, stir evenly, and obtain the soy protein-based adhesive.

[0012] More optimally, the preparation method of the thiolated alumina is: take alumina and ethanol, stir evenly to obtain an alumina solution; take ethanol and deionized water, stir evenly, add the alumina solution, ultrasonically disperse, add (3-mercaptopropyl)trimethoxysilane, react for 22-24 hours, filter, wash, and dry to obtain thiolated alumina.

[0013] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention coats soybean protein-based adhesive on both sides of the surface of the poplar board, and then covers the two sides of the poplar board coated with the soybean protein-based adhesive with kraft paper base paper B, and adds thiolated aluminum oxide to the soybean protein-based adhesive to enhance the bonding force between the poplar board and the kraft paper base paper B.

[0014] 2. The present invention first immerses kraft paper into an acrylic acid-silica sol composite liquid to obtain an impregnated kraft paper A. The acrylic acid-silica sol composite liquid is prepared from thiolated silica sol and acrylic emulsion. The addition of silica sol improves the density of the composite liquid, so that the acrylic acid-silica sol composite liquid has excellent wear resistance, improves the toughness of the coating, and makes the decorative board have good scratch resistance.

[0015] Then, vinyl-modified epoxy resin is coated on both surfaces of the impregnated kraft paper A to obtain kraft paper B. The vinyl in the epoxy resin can react with the thiol in the soy protein-based adhesive to enhance the bonding force between the kraft paper B and the poplar board. DETAILED DESCRIPTION

[0016] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] The sources of the substances involved in the present invention are not particularly limited, and exemplary examples include: epoxy resin: model: E51, which can be purchased from Nantong Xingchen Synthetic Materials Co., Ltd.; soy protein: model: SD-100, which can be purchased from Shansong Biology.

[0018] Embodiment 1: A process for manufacturing a scratch-resistant wooden decorative board, comprising the following steps: Step 1: Preparation of mercaptolated alumina: Take 1g of aluminum oxide and 20mL of ethanol, stir evenly to obtain an aluminum oxide solution; take 60mL of ethanol and 1.2mL of deionized water, stir evenly, add the aluminum oxide solution, ultrasonically disperse, add 1mL of (3-mercaptopropyl)trimethoxysilane, react for 23h, filter, wash, and dry to obtain mercaptolated aluminum oxide; Step 2: Preparation of vinyl modified epoxy resin: Take 75g acrylic acid, 110g epoxy resin, 30g dithiodipropionic acid, 1g tetrabutylammonium bromide, and 0.1g hydroquinone, heat to 92°C and stir for 1.5h, then continue to heat to 107°C and react for 2.5h to obtain a vinyl-modified epoxy resin; Step 3: Preparation of soy protein-based adhesive: Take 500 mL of deionized water, add 4 g of borax, 8 g of sodium sulfite, 145 g of soy protein, and 5 g of thiolated alumina, heat to 57 ° C, stir for 1.5 h, cool to 27 ° C, add 43 g of propylene glycol triglycidyl ether, stir evenly, and obtain a soy protein-based adhesive; Step 4: Preparation of acrylic emulsion: Take 42g of methyl methacrylate, 50g of butyl acrylate, 45g of styrene, and 11g of acrylic acid, mix them evenly to obtain a monomer mixed solution; take 30mL of deionized water, 1.5g of polyoxyethylene nonylphenol ether, and 1.3g of sodium dodecylbenzene sulfonate, stir evenly, heat to 42°C, add the monomer mixed solution dropwise while stirring, and stir for 12min to obtain an emulsion; take 20mL of deionized water, 0.6g of polyoxyethylene nonylphenol ether, 0.5g of sodium dodecylbenzene sulfonate, and 1g of sodium bicarbonate, heat to 86°C, add the emulsion, react for 5.5h, add 24g of dimethylethanolamine dropwise while stirring, and stir for 25min to obtain an acrylic emulsion; Step 5: Preparation of acrylic acid-silica sol composite solution: Preparation of mercapto-silica sol: Take 100 mL of ethanol and 8.5 mL of 25 wt% ammonia water, stir evenly at 65°C, then drop 12 mL of tetraethyl orthosilicate, continue stirring at 62°C for 1.5 h, and age for 35 min to obtain silica sol; Take 9 mL of γ-mercaptopropyltrimethoxysilane and 100 mL of ethanol, stir evenly to obtain a γ-mercaptopropyltrimethoxysilane solution; take silica sol, heat it to 62° C., dropwise add the γ-mercaptopropyltrimethoxysilane solution, stir for 6 hours, and obtain a mercaptolated silica sol; Take 80g of acrylic acid emulsion and 5g of mercapto-silica sol, stir for 1.5h to obtain acrylic acid-silica sol composite liquid; Step 6: Preparation of scratch-resistant wood decorative panels: Take kraft paper and cut it into 10 cm × 10 cm samples, immerse it in acrylic acid-silica sol composite solution for 2.5 hours, and dry it to obtain kraft paper A after impregnation treatment; then coat the two surfaces of the kraft paper A after impregnation treatment with vinyl modified epoxy resin, and the single-side coating amount is 80g / m 2 , drying to obtain kraft paper base B; Take a 2mm×25mm×100mm poplar board and evenly apply the soy protein-based adhesive on both sides of the poplar board. The coating amount on one side is 100g / m 2; Cover the poplar board coated with soybean protein-based adhesive with kraft paper B on both sides, press at 80°C and 2.5 MPa for 10 min, then irradiate with ultraviolet light with a wavelength of 365 nm for 10 s and dry to obtain a scratch-resistant wood decorative board.

[0019] Embodiment 2: A process for manufacturing a scratch-resistant wooden decorative board, comprising the following steps: Step 1: Preparation of mercaptolated alumina: Take 1g of aluminum oxide and 20mL of ethanol, stir evenly to obtain an aluminum oxide solution; take 60mL of ethanol and 1.2mL of deionized water, stir evenly, add the aluminum oxide solution, ultrasonically disperse, add 1mL of (3-mercaptopropyl)trimethoxysilane, react for 22h, filter, wash, and dry to obtain mercaptolated aluminum oxide; Step 2: Preparation of vinyl modified epoxy resin: Take 75g of acrylic acid, 110g of epoxy resin, 30g of dithiodipropionic acid, 1g of tetrabutylammonium bromide, and 0.1g of hydroquinone, heat to 90°C and stir for 1h, then continue to heat to 105°C and react for 2h to obtain a vinyl-modified epoxy resin; Step 3: Preparation of soy protein-based adhesive: Take 500 mL of deionized water, add 4 g of borax, 8 g of sodium sulfite, 145 g of soy protein, and 5 g of thiolated alumina, heat to 55 ° C, stir for 1 h, cool to 25 ° C, add 43 g of propylene glycol triglycidyl ether, stir evenly, and obtain a soy protein-based adhesive; Step 4: Preparation of acrylic emulsion: Take 42g of methyl methacrylate, 50g of butyl acrylate, 45g of styrene, and 11g of acrylic acid, mix them evenly to obtain a monomer mixed solution; take 30mL of deionized water, 1.5g of polyoxyethylene nonylphenol ether, and 1.3g of sodium dodecylbenzene sulfonate, stir them evenly, heat to 40°C, add the monomer mixed solution dropwise while stirring, and stir for 10min to obtain an emulsion; take 20mL of deionized water, 0.6g of polyoxyethylene nonylphenol ether, 0.5g of sodium dodecylbenzene sulfonate, and 1g of sodium bicarbonate, heat to 85°C, add the emulsion, react for 5h, add 24g of dimethylethanolamine dropwise while stirring, and stir for 20min to obtain an acrylic emulsion; Step 5: Preparation of acrylic acid-silica sol composite solution: Preparation of mercapto-silica sol: Take 100 mL of ethanol and 8.5 mL of 25 wt% ammonia water, stir evenly at 60°C, then drop 12 mL of tetraethyl orthosilicate, continue stirring at 60°C for 1 hour, and age for 30 minutes to obtain silica sol; Take 9 mL of γ-mercaptopropyltrimethoxysilane and 100 mL of ethanol, stir evenly to obtain a γ-mercaptopropyltrimethoxysilane solution; take silica sol, heat it to 60°C, dropwise add the γ-mercaptopropyltrimethoxysilane solution, stir for 5 hours, and obtain a mercaptolated silica sol; Take 80g of acrylic acid emulsion and 5g of mercapto-silica sol, stir for 1h to obtain acrylic acid-silica sol composite liquid; Step 6: Preparation of scratch-resistant wood decorative panels: Take kraft paper and cut it into 10cm×10cm samples, immerse it in acrylic acid-silica sol composite solution for 2h, and dry it to obtain kraft paper A after impregnation treatment; then coat the two surfaces of kraft paper A after impregnation treatment with vinyl modified epoxy resin, and the single-side coating amount is 80g / m 2 , drying to obtain kraft paper base B; Take a 2mm×25mm×100mm poplar board and evenly apply the soy protein-based adhesive on both sides of the poplar board. The coating amount on one side is 100g / m 2 ; Cover the poplar board coated with soybean protein-based adhesive with kraft paper B on both sides, press at 80°C and 2.5 MPa for 10 min, then irradiate with ultraviolet light with a wavelength of 365 nm for 10 s and dry to obtain a scratch-resistant wood decorative board.

[0020] Embodiment 3: A process for manufacturing a scratch-resistant wooden decorative board, comprising the following steps: Step 1: Preparation of mercaptolated alumina: Take 1g of aluminum oxide and 20mL of ethanol, stir evenly to obtain an aluminum oxide solution; take 60mL of ethanol and 1.2mL of deionized water, stir evenly, add the aluminum oxide solution, ultrasonically disperse, add 1mL of (3-mercaptopropyl)trimethoxysilane, react for 24h, filter, wash, and dry to obtain mercaptolated aluminum oxide; Step 2: Preparation of vinyl modified epoxy resin: Take 75g acrylic acid, 110g epoxy resin, 30g dithiodipropionic acid, 1g tetrabutylammonium bromide, and 0.1g hydroquinone, heat to 95°C and stir for 2h, then continue to heat to 110°C and react for 3h to obtain a vinyl-modified epoxy resin; Step 3: Preparation of soy protein-based adhesive: Take 500 mL of deionized water, add 4 g of borax, 8 g of sodium sulfite, 145 g of soy protein, and 5 g of thiolated alumina, heat to 60 ° C, stir for 2 h, cool to 30 ° C, add 43 g of propylene glycol triglycidyl ether, stir evenly, and obtain a soy protein-based adhesive; Step 4: Preparation of acrylic emulsion: Take 42g of methyl methacrylate, 50g of butyl acrylate, 45g of styrene, and 11g of acrylic acid, mix them evenly to obtain a monomer mixed solution; take 30mL of deionized water, 1.5g of polyoxyethylene nonylphenol ether, and 1.3g of sodium dodecylbenzene sulfonate, stir evenly, heat to 45°C, add the monomer mixed solution dropwise while stirring, and stir for 15min to obtain an emulsion; take 20mL of deionized water, 0.6g of polyoxyethylene nonylphenol ether, 0.5g of sodium dodecylbenzene sulfonate, and 1g of sodium bicarbonate, heat to 88°C, add the emulsion, react for 6h, add 24g of dimethylethanolamine dropwise while stirring, and stir for 30min to obtain an acrylic emulsion; Step 5: Preparation of acrylic acid-silica sol composite solution: Preparation of mercapto-silica sol: Take 100 mL of ethanol and 8.5 mL of 25 wt% ammonia water, stir evenly at 70 ° C, then add 12 mL of tetraethyl orthosilicate dropwise, continue stirring at 65 ° C for 2 h, and age for 40 min to obtain silica sol; Take 9 mL of γ-mercaptopropyltrimethoxysilane and 100 mL of ethanol, stir evenly to obtain a γ-mercaptopropyltrimethoxysilane solution; take silica sol, heat it to 65° C., dropwise add the γ-mercaptopropyltrimethoxysilane solution, stir for 7 hours, and obtain a mercaptolated silica sol; Take 80g of acrylic acid emulsion and 5g of mercapto-silica sol, stir for 2h to obtain acrylic acid-silica sol composite liquid; Step 6: Preparation of scratch-resistant wood decorative panels: Take kraft paper and cut it into 10cm×10cm samples, immerse it in acrylic acid-silica sol composite solution for 2-3h, dry it, and obtain kraft paper A after impregnation treatment; then coat the two surfaces of kraft paper A after impregnation treatment with vinyl modified epoxy resin, and the single-side coating amount is 80g / m 2 , drying to obtain kraft paper base B; Take a 2mm×25mm×100mm poplar board and evenly apply the soy protein-based adhesive on both sides of the poplar board. The coating amount on one side is 100g / m 2 ; Cover the poplar board coated with soybean protein-based adhesive with kraft paper B on both sides, press at 80°C and 2.5 MPa for 10 min, then irradiate with ultraviolet light with a wavelength of 365 nm for 10 s and dry to obtain a scratch-resistant wood decorative board.

[0021] Comparative Example 1: No thiolated aluminum oxide is added to the soy protein-based adhesive, and the rest is the same as Example 1: Step 1: Preparation of vinyl modified epoxy resin: Take 75g acrylic acid, 110g epoxy resin, 30g dithiodipropionic acid, 1g tetrabutylammonium bromide, and 0.1g hydroquinone, heat to 92°C and stir for 1.5h, then continue to heat to 107°C and react for 2.5h to obtain a vinyl-modified epoxy resin; Step 2: Preparation of soy protein-based adhesive: Take 500 mL of deionized water, add 4 g of borax, 8 g of sodium sulfite, and 145 g of soy protein, heat to 57 ° C, stir for 1.5 h, cool to 27 ° C, add 43 g of glycerol triglycidyl ether, stir evenly, and obtain a soy protein-based adhesive; Step 3: Preparation of acrylic emulsion: Take 42g of methyl methacrylate, 50g of butyl acrylate, 45g of styrene, and 11g of acrylic acid, mix them evenly to obtain a monomer mixed solution; take 30mL of deionized water, 1.5g of polyoxyethylene nonylphenol ether, and 1.3g of sodium dodecylbenzene sulfonate, stir evenly, heat to 42°C, add the monomer mixed solution dropwise while stirring, and stir for 12min to obtain an emulsion; take 20mL of deionized water, 0.6g of polyoxyethylene nonylphenol ether, 0.5g of sodium dodecylbenzene sulfonate, and 1g of sodium bicarbonate, heat to 86°C, add the emulsion, react for 5.5h, add 24g of dimethylethanolamine dropwise while stirring, and stir for 25min to obtain an acrylic emulsion; Step 4: Preparation of acrylic acid-silica sol composite solution: Preparation of mercapto-silica sol: Take 100 mL of ethanol and 8.5 mL of 25 wt% ammonia water, stir evenly at 65°C, then drop 12 mL of tetraethyl orthosilicate, continue stirring at 62°C for 1.5 h, and age for 35 min to obtain silica sol; Take 9 mL of γ-mercaptopropyltrimethoxysilane and 100 mL of ethanol, stir evenly to obtain a γ-mercaptopropyltrimethoxysilane solution; take silica sol, heat it to 62° C., dropwise add the γ-mercaptopropyltrimethoxysilane solution, stir for 6 hours, and obtain a mercaptolated silica sol; Take 80g of acrylic acid emulsion and 5g of mercapto-silica sol, stir for 1.5h to obtain acrylic acid-silica sol composite liquid; Step 5: Preparation of scratch-resistant wood decorative panels: Take kraft paper and cut it into 10 cm × 10 cm samples, immerse it in acrylic acid-silica sol composite solution for 2.5 hours, and dry it to obtain kraft paper A after impregnation treatment; then coat the two surfaces of the kraft paper A after impregnation treatment with vinyl modified epoxy resin, and the single-side coating amount is 80g / m 2 , drying to obtain kraft paper base B; Take a 2mm×25mm×100mm poplar board and evenly apply the soy protein-based adhesive on both sides of the poplar board. The coating amount on one side is 100g / m 2 ; Cover the poplar board coated with soybean protein-based adhesive with kraft paper B on both sides, press at 80°C and 2.5 MPa for 10 min, then irradiate with ultraviolet light with a wavelength of 365 nm for 10 s and dry to obtain a scratch-resistant wood decorative board.

[0022] Comparative Example 2: No mercapto-silica sol was added, and the rest was the same as Example 1: Step 1: Preparation of mercaptolated alumina: Take 1g of aluminum oxide and 20mL of ethanol, stir evenly to obtain an aluminum oxide solution; take 60mL of ethanol and 1.2mL of deionized water, stir evenly, add the aluminum oxide solution, ultrasonically disperse, add 1mL of (3-mercaptopropyl)trimethoxysilane, react for 23h, filter, wash, and dry to obtain mercaptolated aluminum oxide; Step 2: Preparation of vinyl modified epoxy resin: Take 75g acrylic acid, 110g epoxy resin, 30g dithiodipropionic acid, 1g tetrabutylammonium bromide, and 0.1g hydroquinone, heat to 92°C and stir for 1.5h, then continue to heat to 107°C and react for 2.5h to obtain a vinyl-modified epoxy resin; Step 3: Preparation of soy protein-based adhesive: Take 500 mL of deionized water, add 4 g of borax, 8 g of sodium sulfite, 145 g of soy protein, and 5 g of thiolated alumina, heat to 57 ° C, stir for 1.5 h, cool to 27 ° C, add 43 g of propylene glycol triglycidyl ether, stir evenly, and obtain a soy protein-based adhesive; Step 4: Preparation of acrylic emulsion: Take 42g of methyl methacrylate, 50g of butyl acrylate, 45g of styrene, and 11g of acrylic acid, mix them evenly to obtain a monomer mixed solution; take 30mL of deionized water, 1.5g of polyoxyethylene nonylphenol ether, and 1.3g of sodium dodecylbenzene sulfonate, stir evenly, heat to 42°C, add the monomer mixed solution dropwise while stirring, and stir for 12min to obtain an emulsion; take 20mL of deionized water, 0.6g of polyoxyethylene nonylphenol ether, 0.5g of sodium dodecylbenzene sulfonate, and 1g of sodium bicarbonate, heat to 86°C, add the emulsion, react for 5.5h, add 24g of dimethylethanolamine dropwise while stirring, and stir for 25min to obtain an acrylic emulsion; Step 5: Preparation of scratch-resistant wood decorative panels: Take kraft paper and cut it into 10cm×10cm samples, immerse it in acrylic emulsion for 2.5h, and dry it to obtain kraft paper A after impregnation treatment; then coat the two surfaces of kraft paper A after impregnation treatment with vinyl modified epoxy resin, and the single-side coating amount is 80g / m 2 , drying to obtain kraft paper base B; Take a 2mm×25mm×100mm poplar board and evenly apply the soy protein-based adhesive on both sides of the poplar board. The coating amount on one side is 100g / m 2 ; Cover the poplar board coated with soybean protein-based adhesive with kraft paper B on both sides, press at 80°C and 2.5 MPa for 10 min, then irradiate with ultraviolet light with a wavelength of 365 nm for 10 s and dry to obtain a scratch-resistant wood decorative board.

[0023] Comparative Example 3: Using epoxy resin instead of vinyl modified epoxy resin, the rest is the same as Example 1: Step 1: Preparation of mercaptolated alumina: Take 1g of aluminum oxide and 20mL of ethanol, stir evenly to obtain an aluminum oxide solution; take 60mL of ethanol and 1.2mL of deionized water, stir evenly, add the aluminum oxide solution, ultrasonically disperse, add 1mL of (3-mercaptopropyl)trimethoxysilane, react for 23h, filter, wash, and dry to obtain mercaptolated aluminum oxide; Step 2: Preparation of soy protein-based adhesive: Take 500 mL of deionized water, add 4 g of borax, 8 g of sodium sulfite, 145 g of soy protein, and 5 g of thiolated alumina, heat to 57 ° C, stir for 1.5 h, cool to 27 ° C, add 43 g of propylene glycol triglycidyl ether, stir evenly, and obtain a soy protein-based adhesive; Step 3: Preparation of acrylic emulsion: Take 42g of methyl methacrylate, 50g of butyl acrylate, 45g of styrene, and 11g of acrylic acid, mix them evenly to obtain a monomer mixed solution; take 30mL of deionized water, 1.5g of polyoxyethylene nonylphenol ether, and 1.3g of sodium dodecylbenzene sulfonate, stir evenly, heat to 42°C, add the monomer mixed solution dropwise while stirring, and stir for 12min to obtain an emulsion; take 20mL of deionized water, 0.6g of polyoxyethylene nonylphenol ether, 0.5g of sodium dodecylbenzene sulfonate, and 1g of sodium bicarbonate, heat to 86°C, add the emulsion, react for 5.5h, add 24g of dimethylethanolamine dropwise while stirring, and stir for 25min to obtain an acrylic emulsion; Step 4: Preparation of acrylic acid-silica sol composite solution: Preparation of mercapto-silica sol: Take 100 mL of ethanol and 8.5 mL of 25 wt% ammonia water, stir evenly at 65°C, then drop 12 mL of tetraethyl orthosilicate, continue stirring at 62°C for 1.5 h, and age for 35 min to obtain silica sol; Take 9 mL of γ-mercaptopropyltrimethoxysilane and 100 mL of ethanol, stir evenly to obtain a γ-mercaptopropyltrimethoxysilane solution; take silica sol, heat it to 62° C., dropwise add the γ-mercaptopropyltrimethoxysilane solution, stir for 6 hours, and obtain a mercaptolated silica sol; Take 80g of acrylic acid emulsion and 5g of mercapto-silica sol, stir for 1.5h to obtain acrylic acid-silica sol composite liquid; Step 5: Preparation of scratch-resistant wood decorative panels: Take kraft paper and cut it into 10cm×10cm samples, immerse it in acrylic acid-silica sol composite solution for 2.5h, dry it, and obtain kraft paper A after impregnation treatment; then coat the two surfaces of kraft paper A after impregnation treatment with epoxy resin, and the coating amount on one side is 80g / m 2 , drying to obtain kraft paper base B; Take a 2mm×25mm×100mm poplar board and evenly apply the soy protein-based adhesive on both sides of the poplar board. The coating amount on one side is 100g / m 2 ; Cover the poplar board coated with soybean protein-based adhesive with kraft paper B on both sides, press at 80°C and 2.5 MPa for 10 min, then irradiate with ultraviolet light with a wavelength of 365 nm for 10 s and dry to obtain a scratch-resistant wood decorative board.

[0024] experiment: The scratch-resistant wooden decorative panels prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to performance tests. Referring to GB / T17657-2022, the scratch-resistant wooden decorative panels were immersed in hot water at 65°C for 3 hours, taken out and cooled for 10 minutes, and the bonding strength between the wood and the kraft paper was tested; five scratching rods with a diameter of 7 mm were used to scratch the wooden decorative panels under different loads to test the load when the surface of the wooden decorative panels was scratched, so as to characterize its scratch resistance. The obtained data are shown as follows: Experiment: In comparative example 1, mercaptolated aluminum oxide is not added to the soy protein-based adhesive, and the bonding strength between the poplar board and the kraft paper B decreases. In comparative example 2, mercaptolated silica sol is not added, and the scratch resistance of the decorative board decreases. In comparative example 3, epoxy resin is used instead of vinyl-modified epoxy resin, and the bonding strength between the poplar board and the kraft paper B decreases, and the scratch resistance decreases slightly. In embodiments 1 to 3 of the present invention, the kraft paper is first immersed in an acrylic acid-silica sol composite liquid to obtain an impregnated kraft paper A. The addition of mercaptolated silica sol increases the density of the composite liquid, so that the acrylic acid-silica sol composite liquid has excellent wear resistance, improves the toughness of the coating, and makes the decorative board have good scratch resistance. Then, vinyl-modified epoxy resin is coated on both surfaces of the impregnated kraft paper A to obtain kraft paper B. The vinyl in the epoxy resin can react with the thiol in the soy protein-based adhesive to enhance the bonding strength between the kraft paper B and the poplar board.

[0025] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A process for manufacturing a scratch-resistant wooden decorative board, characterized in that: The following steps are involved: Step 1: Take acrylic emulsion and mercapto-silica sol, stir for 1-2 hours to obtain acrylic acid-silica sol composite liquid; Step 2: Take acrylic acid, epoxy resin, dithiodipropionic acid, tetrabutylammonium bromide, and hydroquinone, heat to 90-95°C and stir for 1-2h, and continue to heat to 105-110°C for reaction for 2-3h to obtain a vinyl-modified epoxy resin; Step 3: Take kraft paper, immerse it in acrylic acid-silica sol composite solution for 2-3 hours, and dry it to obtain kraft paper A after impregnation treatment; then coat vinyl-modified epoxy resin on both surfaces of the kraft paper A after impregnation treatment, and dry it to obtain kraft paper B; Step 4: Take a poplar board and evenly apply the soy protein-based adhesive on both sides of the surface of the poplar board, cover both sides of the poplar board coated with the soy protein-based adhesive with kraft paper B, press at 80-85°C for 10-15 minutes, then irradiate with ultraviolet light for 10-15 seconds, and dry to obtain a scratch-resistant wooden decorative board.

2. The manufacturing process of a scratch-resistant wooden decorative board according to claim 1, characterized in that: In step 1, the preparation method of acrylic emulsion is as follows: take methyl methacrylate, butyl acrylate, styrene and acrylic acid, mix them evenly to obtain a monomer mixed solution; take deionized water, polyoxyethylene nonylphenol ether and sodium dodecylbenzene sulfonate, stir them evenly, heat them to 40-45° C., add the monomer mixed solution dropwise while stirring, stir for 10-15 minutes, and obtain an emulsion; take deionized water, polyoxyethylene nonylphenol ether, sodium dodecylbenzene sulfonate and sodium bicarbonate, heat them to 85-88° C., add the emulsion, react for 5-6 hours, add dimethylethanolamine dropwise while stirring, and stir for 20-30 minutes to obtain an acrylic emulsion.

3. The manufacturing process of the scratch-resistant wooden decorative board according to claim 1, characterized in that: In step 1, the mass ratio of acrylic emulsion to mercapto-silica sol is (80-85):

5.

4. The manufacturing process of the scratch-resistant wooden decorative board according to claim 1, characterized in that: In step 1, the preparation method of mercaptolated silica sol is: take γ-mercaptopropyltrimethoxysilane and ethanol, stir evenly to obtain γ-mercaptopropyltrimethoxysilane solution; take silica sol, heat it to 60-65°C, add γ-mercaptopropyltrimethoxysilane solution dropwise, stir for 5-7h, and obtain mercaptolated silica sol.

5. The manufacturing process of the scratch-resistant wooden decorative board according to claim 4, characterized in that: The preparation method of the silica sol is as follows: take ethanol and ammonia water, stir them evenly at 60-70° C., then drop tetraethyl orthosilicate, continue stirring at 60-65° C. for 1-2 hours, and age for 30-40 minutes to obtain the silica sol.

6. The manufacturing process of the scratch-resistant wooden decorative board according to claim 1, characterized in that: In step 4, the preparation method of the soy protein-based adhesive is as follows: take deionized water, add borax, sodium sulfite, soy protein, and thiolated alumina, heat to 55-60°C, stir for 1-2h, cool to 25-30°C, add propylene glycol triglycidyl ether, stir evenly, and obtain the soy protein-based adhesive.

7. The manufacturing process of the scratch-resistant wooden decorative board according to claim 6, characterized in that: The preparation method of the mercaptolated aluminum oxide is as follows: taking aluminum oxide and ethanol, stirring evenly to obtain an aluminum oxide solution; taking ethanol and deionized water, stirring evenly, adding the aluminum oxide solution, ultrasonically dispersing, adding (3-mercaptopropyl)trimethoxysilane, reacting for 22-24 hours, filtering, washing, and drying to obtain the mercaptolated aluminum oxide.

8. The scratch-resistant wooden decorative board manufactured according to the manufacturing process of the scratch-resistant wooden decorative board according to any one of claims 1 to 7.